Detection of Isim in Al-Qur'anic Verses using the Isim Marking Method and Creating Hyperlinks to Support the Quranpedia Website Project - Muhamad Jibril; Eko Darwiyanto; Moch Arif Bijaksana (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
This research aims to detect isim words containing "???" (Alif Lam) in the verses of the Al-Qur'an using the isim marking method and creating hyperlinks to support the Quranpedia website project. The research follows the Agile methodology in project development. The findings reveal that approximately 12.97% of words in the Al-Qur'an contain "???" (Alif Lam). This information provides valuable insights into the frequency and distribution of isim words in the Al-Qur'an and reinforces support for the Quranpedia project.